Semarang Venesia dari Timur Hingga Semarang Pesona Asia: Perubahan Kebijakan Pembangunan Kota Semarang - Sri Suwitri (Jurnal Aplikasi Manajemen, 2010)
Changing governance regards changing public policy about Semarang City development. Changing Semarang City development policy has changed aesthetical Semarang City as Venetian of East or de oude stad as city which currently was nicknamed by Semarang, The Beauty of Asia (SPA). Changing governance also change city development policy towards farm purpose as region of diffusion and refores¬ tation toward housing development, about shop and industry, so city development policy faces about problem flooding from river and sea. Changing governance regards changing public policy about Semarang City development. ChangingSemarang City development policy has changed aesthetical Semarang City as Venetian of East or de oude stad as city which currently was nicknamed by Semarang, The Beauty of Asia (SPA). Changing governance also change city development policy towards farm purpose as region of diffusion and refores tation toward housing development, about shop and industry, so city development policy faces about problem flooding from river and sea.